Enantioselective Radical Addition/Cross‐Coupling of Organozinc Reagents, Alkyl Iodides, and Alkenyl Boron Reagents. Issue 40 (28th August 2019) - Chierchia, Matteo; Xu, Peilin; Lovinger, Gabriel J.; Morken, James P.
Abstract: A hybrid transition‐metal/radical process is described that results in the addition of organozinc reagents and alkyl halides across alkenyl boron reagents in an enantioselective catalytic fashion. The reaction can be accomplished both intermolecularly and intramolecularly, providing useful product yields and high enantioselectivities in both manifolds. Abstract : A radical hybrid : The dicarbofunctionalization of vinylB(pin) was achieved through the use of a nickel‐based chiral catalyst. The reaction employs alkyl halide and organozinc reagents and can be accomplished with good levels of enantioselectivity in an intra‐ or intermolecular fashion.